THE NEED TO FORM PERSONAL VALUES IN STUDENTS IN EDUCATIONAL CLASSES BASED ON THE AXIOLOGICAL APPROACH - Askaraliyeva, Mukhtasar (Журнал иностранных языков и лингвистики, 2024)
In this article, the importance of education today, the study of the education and internal potential of a person aimed at the comprehensive improvement of a person in society in recent years, and the development of moral views, human qualities, and personal values ​​in students of general secondary schools. It was thought that it is necessary to strengthen its national and international foundations by providing knowledge and information to students based on modern requirements and world standards. Problems and issues of education - the fact that it has a greater place than the system of ideas in all periods of human history, human consciousness, faith thoughts are gathered that the struggles for the youth are manifested in the form of influencing the youth through educational methods. became the main goal, how important values ​​are and the formation of personal values.